Manajemen Perpajakan di Perusahaan Pallet Kayu: Studi Kasus PT XYZ - Amelia, Denta; Mirani, Anindyta Najwa; Putra, Muhammad Syahreza; Imani, Puti Syifa; Salsabila, Siti Aliyah; Irawan, Ferry (PT WIM Solusi Prima, 2024)
Tax is a payment obligation to the state, which can reduce a company's net income. Therefore, companies implement tax management to minimize the tax burden paid to the government by the company. Tax management also aims to avoid sanctions in the form of criminal sanctions or administrative sanctions. Therefore, the activities are implemented by many companies, including PT XYZ which operates in the field of processing raw materials in the form of wood. The aim of this research is to find out how tax management is implemented in the timber sector, as well as the implementation of company tax obligations. The research results show the following results. First, PT XYZ has implemented tax management well and has not violated applicable regulations. Second, PT XYZ applies the calculation of PPh Article 21 using the net method. Third, there is an underpayment of VAT because it is easier for companies to redistribute the lack of funds. Fourth, the company also applies the calculation of PPh Article 23 which imposes a tax rate on rental goods. Fifth, the company calculates its corporate income tax using the bookkeeping method. Regarding PPh 25, payment is made in installments to reduce the burden of paying taxes in full and directly.